Upaya Pencegahan Kekerasan Terhadap Anak dimasa Pandemi Covid-19 - Ni Made Wismantari; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2021)
The Covid-19 pandemic has had the worst impact, namely the increased vulnerability of children to become victims of violence. The Covid-19 pandemic has stimulated an increase in cases of violence against children, so in this case a legal protection is needed to fulfill the rights obtained for every child. The purposes of this study are to reveal legal arrangements in an effort to prevent violence against children during the COVID-19 pandemic as well as legal protection for children who experience violence during the COVID-19 pandemic. The research method used in this research is normative legal research with a statutory approach. The technique of collecting legal materials used in this research is the study of documents or library materials. The sources of legal materials used are primary and secondary sources of legal materials. The data analysis techniques were analyzed qualitatively and presented descriptively. The results of the study revealed that the government's efforts to prevent violence against children during the Covid-19 Pandemic were pursued through preventive legal protection with the aim of preventing violations before the occurrence of violations and repressive legal protection in the form of sanctions such as fines, imprisonment, and additional penalties given if a dispute has occurred or has occurred. a violation is committed. All parties, both families and the government, should try to protect children from all acts of violence.